Comparison of fibrin adhesives prepared by 3 different methods - Cavichiolo, Juliana Benthien; Buschle, Maurício; Carvalho, Bettina (International Archives of Otorhinolaryngology, 2013)
Introduction: Fibrin tissue adhesive, which has applications in several areas of medicine, can be prepared by different methods. Aim: To compare fibrin tissue adhesives prepared by 3 different methods. Method: In this prospective experimental laboratory study, fibrin tissue adhesives prepared by the use of plasma fibrinogen (group 1), cryoprecipitation (group 2), and precipitation by ammonium sulfate (group 3) were tested on 15 rabbits and 10 fragments of dura mater. The quality of the clots was assessed in terms of the success of the healing process, local toxicity, graft adhesion capacity, and degree of adhesion of 2 fragments of dura mater produced. Results: All methods produced a clot with high adhesion and no toxicity, but tensile strength testing revealed that the glue produced from the ammonium sulfate-precipitated clot (group 3) was the strongest, requiring 39 g/cm2 to separate the fragments as opposed to 23 g/cm2 for group 2 and 13 g/cm2 for group 1. Conclusion: All methods produced good results as far as clot formation and non-toxicity, but ammonium sulfate precipitation produced the best tensile strength and was thus the most effective method of preparing fibrin tissue adhesive.
Keywords: Fibrin; Fibrin Tissue Adhesive; Biological Therapy; Fibrinogen; Plasma